Development Of Framework For Building Change Information Modelling (BCIM) - Leong, Kar Kang (2020)
Construction change is an important aspect of the project, as changes often result in time delays, cost overruns, quality defects, negative impacts and very often lead to disputes. Related to this, many initiatives have been proposed to mitigate the impact brought about by changes. One of the methods is to leverage digitalised construction, such as Building Information Modelling (BIM). BIM has transformed the construction project into a digital construction, in the form of virtual 3D building in which provides detailed information as well as identifying their relationship between objects. The research aims to develop a Building Change Information Modelling (BCIM) for managing changes in construction project. These existing researches often focused mainly on visualization and identification of change without being completely integrated with BIM. The research attempts to identify the current practices in the construction industry with a view to develop an integrated framework. Central Limit Theorem was adopted in this research to ensure the reliability and validity of the data. A total of ninety-seven sets of questionnaire responses were used in the research and a total of three interviewees were successfully interviewed who working as a quantity surveyor in a consultancy firm in the Klang Valley area. The interview and questionnaire surveys were conducted to solicit the current practices of change management and BIM, including the shortcoming of current practices. This research identified nine essential features that must be included in the BCIM system. The nine features, including facilitating knowledge capture and sharing from BIM model and process, developing a standard change procedure, comparing two revisions of models, showing updated components to the original model with reason of changing, remaining data confidential, cloud-based to enhance data interoperability, synchronizing data on a serve with mobile device application, integrating BIM and change management, and integrating the company’s database with the proposed system. In addition, the findings also revealed that there was a significant difference in the perception between the respondent groups about the benefits of BIM, to improve information flow. In more details, the category with less than five years working experience has been defined as a significant difference category on the perceptions of BIM has been able to improve information flow. This research is expected to develop an integrated framework to enhance the performance of project design changes, improve coordination with all parties and manage the project efficiently throughout the project lifecycle.